The effect of topical ocular moxifloxacin on conjunctival and nasal mucosal flora - Celebi, Ali Riza Cenk; Celebi, Ozlem Onerci (NATURE RESEARCH, 2021)
To determine the short-term effect of topically administered ocular moxifloxacin on conjunctival and nasal bacterial mucosal flora. The study included 20 patients with newly diagnosed age-related macular degeneration. Each patient's diseased eye was selected as the treatment eye and the fellow eye was selected as the control eye. All treatment eyes constituted the treatment group and all controls eyes constituted the control group. All patients received intravitreal injection of ranibizumab. Cultures were obtained from the inferior conjunctival fornix and the nostrils in all patients. Patients were instructed to administer moxifloxacin eye drops to the treatment eye 4 times daily for 1 week. The patients were instructed to come for a follow-up exam 1 week post intravitreal injection. The bacterial culture positivity rate and the bacteria isolated from the conjunctiva and nostrils were recorded in the 2 groups before and after use of topical ocular moxifloxacin. Mean age of the patients (12 female and 8 male) was 64.9 years. Before use of topical ocular moxifloxacin the conjunctival and nasal culture positivity rates in the treatment group were both 100\%, versus 90\% and 95\%, respectively, in the control group. At the follow-up exam the conjunctival and nasal mucosa culture positivity rates in the treatment group decreased to 20\% (4/20) and 30\% (6/20), respectively (P<0.001), versus 85\% (17/20) and 80\% (16/20), respectively, in the control group (P=0.68 and P=0.72 for conjunctival and nasal). This is the first study to show that moxifloxacin applied to the ocular surface topically has a significant effect on nasal flora. Daily administration of topical ocular moxifloxacin for 1 week significantly reduces the nasal bacterial flora in addition to conjunctival flora.